PENGARUH REVIEW SERVICE MENU DAN RATING MENU TERHADAP KEPUTUSAN PEMBELIAN MAKANAN PADA MARKETPLACE SHOPEEFOOD - Mrs Istiqomah; Lina Mufidah (Jurnal Socia Akademika, 2021)
Technology continues to develop, including transaction technology; currently, there is a change of digital era that can also shift the behavior of offline customers who can now shop online. The study aims to find out how influential menu reviews and menu ratings affect food buying decisions. The research method uses quantitative with this type of causal research. Data collection uses surveys through questionnaire sheets written in Google Form. The population in this study is respondents who actively use shopee food applications. The sample numbered 100 respondents who met the criteria. Data analysis techniques use multiple linear regressions. The results stated that (1) Online Consumer Rating had no positive and significant effect on shopee food purchasing decisions; (2) the review service has a positive and significant influence on shopee food purchasing decisions; and (3) statistical test results with F tests obtained simultaneously independent variables, namely menu review services and rating services give an influence on buying decisions by 0.148 describing 14.8% while other variables outside the study explain the other 85.2